2022
DOI: 10.1007/s12011-022-03344-x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Fetal Programming in Ewe Nutrition with Chromium Propionate or Calcium Salts of Palm Oil on the Meat Quality and Bone of the Progeny

Abstract: This study aimed to evaluate the inclusion of chromium propionate or calcium salts of palm oil in ewes' diet in the nal third of gestation and lactation on the effects of progeny performance, carcass characteristics, non-carcass components, and bone density. Forty-three ewe, Santa Inês and Dorper breeds, 3 ± 1 years old and weighing 57 ± 10 kg were used. The ewes were distributed in causal blocks in three treatments, CTL treatment (n = 15) with starch from corn; CR (n = 15) diet CTL plus chromium propionate; P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Lambs from FMG treatment had a lower empty body weight. Interestingly, Brochine et al [ 45 ] used chromium propionate and calcium salts during gestation, and they reported that the weight of non-carcass components of lambs was heavier than control groups. Also, the authors reported that chromium propionate during maternal supplementations affects lambs’ respiratory tract and spleen development.…”
Section: Discussionmentioning
confidence: 99%
“…Lambs from FMG treatment had a lower empty body weight. Interestingly, Brochine et al [ 45 ] used chromium propionate and calcium salts during gestation, and they reported that the weight of non-carcass components of lambs was heavier than control groups. Also, the authors reported that chromium propionate during maternal supplementations affects lambs’ respiratory tract and spleen development.…”
Section: Discussionmentioning
confidence: 99%